DIVERSIFICATION AS A GREEN APPROACH TO AGRICULTURAL DEVELOPMENT - Minbayeva Aygul Utepbergen qizi (Web of Journals Publishing, 2025)
The abstract provides a concise summary of the paper's objectives, methods, results, and conclusions. In this case, it would explain how diversifying agricultural production can enhance resilience against climate risks. This section might include key methods, such as crop rotation, agroforestry, and integrated pest management, highlighting their potential to reduce vulnerability to climate impacts like droughts, floods, and temperature extremes.
Keywords: Agricultural diversification, climate resilience, crop rotation, climate change adaptation, sustainable agriculture.